A Regional Experience of Adult Granulosa Cell Tumours: A Retrospective Analysis - Joanne Moffatt; Jo Morrison; Srividya Sundararajan; Rebecca Newhouse; Laura Atherton; Jonathan Frost; Philip Rolland; Kirsty Milford; Katharine Edey; Jane Borley; Amy Sanders; Axel Walther; et al. (Onco, 2025)
Background: Adult granulosa cell tumours (AGCT) of the ovary account for 2–5% of ovarian tumours, with 30% occurring in women of childbearing age. Despite a good prognosis, up to 25% recur. There is a paucity of high-quality evidence to guide management. Objective: To describe management of AGCT across multiple gynaecological cancer centres. Methods: Retrospective analysis of electronic patient records from six gynaecological cancer centres in Southwest England between 2000 and 2021 (n = 119). Results: We included 107 patients with a median follow-up of 60 months (0–261 months). Most (97/107; 90.7%) were diagnosed with stage I disease (31.8% stage Ic). Primary management was staging surgery in 33/107 (30.8%), hysterectomy and bilateral salpingo-oophorectomy (BSO) (28/107; 26.2%), or conservation of an ovary (17/107; 15.9%). Three had a subsequent pregnancy. A quarter (27/107; 25.2%) were diagnosed with recurrent disease. Fifteen patients (15/107; 14%) had multiple recurrences. Recurrence was more likely if cyst rupture was reported at surgery (38.7%) compared with no rupture (14.3%; p < 0.001). The recurrence rate was higher with ovarian conservation (6/17; 35.3%) compared with BSO (21/90; 23.3%; p < 0.01), and all recurrences involved the residual ovary. Of the 11 deaths, 6 (54.5%) were attributed to progressive disease. Conclusions: Although survival with early-stage disease is good, ovarian cystectomy or unilateral ovarian conservation was associated with increased risk of recurrence. There is no conclusive evidence to support a contralateral oophorectomy in pre-menopausal women, but completion surgery should at least be considered, either immediately or after childbearing/assisted reproductive treatment.